2015
DOI: 10.14488/bjopm.2015.v12.n2.a11
|View full text |Cite
|
Sign up to set email alerts
|

The Design Thinking and the Health Services: The Competitive Differential Through the Humanization of Patient Experience

Abstract: It is necessary to rethink the different experiences of patients in health care area. Feelings such as anxiety and fear, for example, are common in the interactions between caregivers and patients, which reflect the disparity between the offered and the necessary to meet the patients' demands. In this article, there will be analyzed two cases of successful application of the Design Thinking in the Health Care area, the "Mayo Clinic" -elected the best hospital in the USA in 2014 -and the "Humanization of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Emotions in patient experience are more relevant than in any other context. Generally speaking, negative emotions are the prevailing trend in the continuum of care (Caulliraux & Meiriño, 2015). These heightened emotions are elicited due to the threat of losing valued resources, such as well-being, money or time that patients experience.…”
Section: Patient Experience As An Emotional Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotions in patient experience are more relevant than in any other context. Generally speaking, negative emotions are the prevailing trend in the continuum of care (Caulliraux & Meiriño, 2015). These heightened emotions are elicited due to the threat of losing valued resources, such as well-being, money or time that patients experience.…”
Section: Patient Experience As An Emotional Processmentioning
confidence: 99%
“…While design is a process with different stages (Roozenburg & Cross, 1991), the entire design process is based on identifying meaningful insights that have the capacity to lead to successful new solutions (Caulliraux & Meiriño, 2015). One of the most effective ways to capture such insights is to focus on the customer experience.…”
Section: Introductionmentioning
confidence: 99%
“…Service design was first introduced at Maggie's Cancer Caring Centre in the UK in 1996 to create a comfortable hospital environment for patients. Since then, it has been used to improve patient experience in healthcare services [6][7][8]. A previous study reported the benefits of applying service design to the healthcare field [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, service design has been actively used to improve the quality of patient care in the field of public health. [Caulliraux AA, Meiriño MJ. 2015;Martin D et al, 2019].…”
mentioning
confidence: 99%